Pemilihan Tetua Berdasarkan Nilai Pemuliaan Komponen Tandan Progeni Dura x Tenera - Annisa Sitepu; Yurna Yenni; Sujadi (Pusat Penelitian Kelapa Sawit, 2022)
Breeding value is the average effect of genes transmitted from parents to their offspring. It can be used as a selection criterion to select superior genotypes. The purpose of this study is to evaluate the performance of the parents through their progenies. The observations were conducted using 21 Dura x Tenera progenies planted in Dolok Sinumbah, PT. Perkebunan Nusantara IV, North Sumatra. Based on the dura’s breeding value, D5 and D6 have the potential to produce offspring that have thick mesocarp with high oil content. On the other hand, T1 tenera has the potential to produce F1 hybrids that have thick mesocarp to fruit with thin shells. The T5 and T6 teneras can be used to produce hybrids with high oil content.